2016
DOI: 10.1016/j.triboint.2015.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the behaviour of silver as a low friction coating in aerospace fasteners

Abstract: Nuts and bolts used in aero-engines are manufactured from heat-resistant super-alloys. When used in a like on like couple, these materials have a high coefficient of friction, and frequently seizure occurs. In order to prevent this, a silver coating is applied to the nut threads, providing a low friction boundary at the interface. Additionally, a radial crimp is applied to the nut, in order to provide a self-locking feature preventing vibration self-loosening. In this study, the coefficient of friction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…An effective method of improving the friction and wear behavior of 20CrMnTi is to prepare 20CrMnTi-based selflubricating composites containing solid lubricants, such as graphene, [12][13][14] carbon nanotubes (CNTs), 15,16 and silver. 17,18 Zhai et al 12 explored the mechanical and tribological behaviors of a Ni 3 Al-multilayer graphene composite. Their results indicated that multilayer graphene enhanced the mechanical properties of a Ni 3 Al-based composite.…”
Section: Introductionmentioning
confidence: 99%
“…An effective method of improving the friction and wear behavior of 20CrMnTi is to prepare 20CrMnTi-based selflubricating composites containing solid lubricants, such as graphene, [12][13][14] carbon nanotubes (CNTs), 15,16 and silver. 17,18 Zhai et al 12 explored the mechanical and tribological behaviors of a Ni 3 Al-multilayer graphene composite. Their results indicated that multilayer graphene enhanced the mechanical properties of a Ni 3 Al-based composite.…”
Section: Introductionmentioning
confidence: 99%
“…Solid self-lubricating coatings are mainly employed to control friction and wear, especially under harsh application conditions, such as aerospace, high vacuum, high speeds, high pressure, and very low or high temperatures [10,11]. Under extreme conditions, conventional lubricants cannot provide the desired performance or durability, and in some cases, they cannot be used.…”
Section: Introductionmentioning
confidence: 99%
“…5 The use of Ag within the aerospace industry has been primarily in fasteners, where low-friction Ag-coated self-locking nuts are used in the demanding conditions within aerospace engines. 6 Furthermore, as a relatively noble metal, it is corrosion resistant, a desirable material property for applications in highly corrosive environments.…”
Section: Introductionmentioning
confidence: 99%